Hopi dwellings : architectural change at Orayvi - Cameron, Catherine M. (University of Arizona Press, 1999)
"The Dramatic Split of the Hopi community of Orayvi in 1906 had lasting consequences not only for the people of Third Mesa but also for the very buildings around which they centered their lives. This book examines architectural and other effects of that split, using architectural change as a framework with which to understand social and cultural processes at prehistoric Southwestern pueblos."--Jacket